ANALISIS KESULITAN BELAJAR SISWA KELAS V SEKOLAH DASAR DA-LAM OPERASI HITUNG SATUAN PANJANG - I Gusti Gede Dwiyana; I Wayan Mardika; I Kadek Yuda Pranata; I Made Sujana Adnyana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to conduct an in-depth analysis of the learning difficulties experienced by fifth-grade elementary school students in solving length unit calculations. The background of this study is based on students’ still-low ability to understand basic concepts of length units and to convert between units, which leads to errors in solving math problems. This study employs a qualitative approach using a descriptive method. The research subjects were fifth-grade students at a selected elementary school chosen through purposive sampling. Data collection techniques included written tests, in-depth interviews, and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that students’ learning difficulties encompass three main aspects: conceptual difficulties, procedural difficulties, and difficulties in problem-solving. Conceptual difficulties are evidenced by students’ low understanding of the relationships between units of length. Procedural difficulties are evident in errors when performing conversion steps and arithmetic operations. Meanwhile, difficulties in problem-solving were evident in students’ inability to understand word problems related to units of length. Additionally, misconceptions were identified, such as errors in using the unit conversion ladder and inaccuracies in determining the appropriate operations to use. Factors contributing to learning difficulties include internal factors